The Use of Financial and Credit Tools to Minimize the Risks in the Organization of Production - Muftahova, Olga; Nechaev, Andrey; Antipina, Oksana (International Journal of Economics and Financial Issues, 2015)
The article describes such form of financing as import revolving leveraged leasing for the purpose of fixed assets modernization. Mathematical modeling techniques are applied in the research. According to the results of the study, the mathematical model of the generalized method of the lease payment calculation is suggested by the authors. The presented method combines several types of leasing. The novelty of this method lies in the fact that on the basis of suggested leasing types the amount of the lease payment is calculated taking into account insurance, financial and currency risks aimed at minimizing losses at downtime due to the limited use of the basic production assets of the company in the production process organization. The authors suggest calculating the payment amount using a floating rate of interest. This proprietary methodology is designed to minimize the risk of production equipment downtime, which ultimately will enable to provide the stability and continuity of the production process. Keywords: leasing payment; leveraged leasing; revolving leveraged leasing. JEL Classifications: C02; C69; G31; G32